2021
DOI: 10.3390/cancers13102500
|View full text |Cite
|
Sign up to set email alerts
|

Harnessing CD16-Mediated NK Cell Functions to Enhance Therapeutic Efficacy of Tumor-Targeting mAbs

Abstract: Natural killer (NK) cells hold a pivotal role in tumor-targeting monoclonal antibody (mAb)-based activity due to the expression of CD16, the low-affinity receptor for IgG. Indeed, beyond exerting cytotoxic function, activated NK cells also produce an array of cytokines and chemokines, through which they interface with and potentiate adaptive immune responses. Thus, CD16-activated NK cells can concur to mAb-dependent “vaccinal effect”, i.e., the development of antigen-specific responses, which may be highly rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(30 citation statements)
references
References 248 publications
(353 reference statements)
1
28
0
1
Order By: Relevance
“…Combining adoptive NK cell therapy with daratumumab is an interesting approach to circumvent the acquired immune suppression in MM patients. The presence of CD16a, the low-affinity receptor for IgG1 and IgG3, on the surface of NK-cells is crucial for ADCC-dependent cell killing by tumor-targeting mAbs [ 32 ]. Depending on the expansion and culture conditions, this CD16a expression can decrease, but the combined use of expanded NK-cells (from umbilical cord blood or peripheral blood) with daratumumab shows encouraging results in preclinical studies [ 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Combining adoptive NK cell therapy with daratumumab is an interesting approach to circumvent the acquired immune suppression in MM patients. The presence of CD16a, the low-affinity receptor for IgG1 and IgG3, on the surface of NK-cells is crucial for ADCC-dependent cell killing by tumor-targeting mAbs [ 32 ]. Depending on the expansion and culture conditions, this CD16a expression can decrease, but the combined use of expanded NK-cells (from umbilical cord blood or peripheral blood) with daratumumab shows encouraging results in preclinical studies [ 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, it has also been proposed that under specific chronic inflammatory conditions of cancer, TAMs protect tumour cells from NK cytotoxicity by preventing the shedding of membrane-bound CD16 ( 108 ). CD16 is an Fc receptor whose shedding indicates NK cell activation and increases NK engagement with target cells ( 109 ). While the maintenance of surface CD16 indicates inhibition of NK cell function, it is worth noting that simultaneously, CD16 acts as an important activating receptor in antibody-dependent cytotoxicity, and it is a well-explored therapeutic target ( 110 ).…”
Section: Context-specific Mechanisms Driving Altered Nk Cell Phenotypes In the Tumour Microenvironmentmentioning
confidence: 99%
“…NK cells are the ideal candidate for adoptive therapy combined with mAbs targeting specific tumor antigens due to their unique mechanism of target cell lysis through ADCC mediated by their CD16 (FcγRIIIa) receptors ( 20 ). Multiple preclinical studies have shown the benefit of NK cells and mAbs in pediatric sarcomas ( 21 23 ).…”
Section: Therapeutic Enhancement Of Nk Cell Functions Via Adccmentioning
confidence: 99%
“…Inclusion criteria based on the presence of predictive biomarkers identifying patients who would likely respond to these mAb are needed to determine the utility of these agents. The clinical response to mAb is also affected by a single nucleotide polymorphism in the FCGR3A (CD16) gene that affects binding affinity for IgG (increased affinity with valine at FCGR3A-158) ( 20 ).…”
Section: Therapeutic Enhancement Of Nk Cell Functions Via Adccmentioning
confidence: 99%
See 1 more Smart Citation